2016
DOI: 10.1002/dys.1527
|View full text |Cite
|
Sign up to set email alerts
|

A Special Font for People with Dyslexia: Does it Work and, if so, why?

Abstract: In 2008 Christian Boer, a Dutch artist, developed a special font ("Dyslexie") to facilitate reading in children and adults with dyslexia. The font has received a lot of media attention worldwide (e.g., TheGuardian.com, Slate.com, TheAtlantic.com, USA Today, and io9.com). Interestingly, there is barely any empirical evidence for the efficacy of Dyslexie. This study aims to examine if Dyslexie is indeed more effective than a commonly used sans serif font (Arial) and, if so, whether this can be explained by its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
(44 reference statements)
5
37
4
1
Order By: Relevance
“…This was an expected result since in this unusual spacing condition, it is difficult to segment sentences into words because the sizes of the (increased) inter-letter and the (default) inter-word spacing appeared similar. However, contrary to several studies (Bachmann, 2013;Marinus et al, 2016;Zorzi et al, 2012), but in line with other previous research (Damiano, Gena, & Venturini, 2019;Kuster et al, 2017), a general advantage in reading speed due to increased spacing, in both its components, was not found either in children with dyslexia or in typical readers. The difference between default and increased spacing employed in the present study was smaller than that used in the study by Zorzi et al (2012), where the authors, using exceptionally wider spacing, found a positive effect on fluency in Italian and French readers.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This was an expected result since in this unusual spacing condition, it is difficult to segment sentences into words because the sizes of the (increased) inter-letter and the (default) inter-word spacing appeared similar. However, contrary to several studies (Bachmann, 2013;Marinus et al, 2016;Zorzi et al, 2012), but in line with other previous research (Damiano, Gena, & Venturini, 2019;Kuster et al, 2017), a general advantage in reading speed due to increased spacing, in both its components, was not found either in children with dyslexia or in typical readers. The difference between default and increased spacing employed in the present study was smaller than that used in the study by Zorzi et al (2012), where the authors, using exceptionally wider spacing, found a positive effect on fluency in Italian and French readers.…”
Section: Discussionsupporting
confidence: 78%
“…The repetition of the same text across the 8 conditions was avoided in order to prevent learning effects. Following the same procedure used by Marinus et al (2016) to combine texts and conditions, we generated two Latin square matrices, one for the texts (12345678,23456781,34567812,45678123,56781234,67812345,78123456,81234567) and a second one for the conditions (ADEHCBGF, BCFGDAHE, GFCBEHAD, HEDAFGBC, EBGDAFCH, FAHCBEDG, CHAFGDEB, DGBEHCFA). This resulted in 64 (8 × 8) different text and condition combinations, each one randomly assigned to a child.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That OpenDyslexic has no effect on legibility and readability was also reported by Zikl et al (2015). Marinus et al (2016) confirmed that the Dyslexie typeface does not provide a benefit when read by people with dyslexia compared with Arial.…”
Section: Typefacesupporting
confidence: 62%
“…A noise manipulation, rather than, e.g., a comparison of different fonts, was applied since noise levels can be easily manipulated and quantified (i.e., in terms of the number of displaced pixels). In contrast, a direct comparison of fonts is more difficult because the contrast of proportional vs. mono-spaced font is confounded with many other visual differences like total stimulus width (Hautala, Hyönä, & Aro, 2011;Marinus et al, 2016). In addition, the 0% noise stimuli allowed us to replicate our original behavioral finding.…”
Section: Word Recognition Behavior Under Conditions Of Visual Noisementioning
confidence: 82%